Optimization of extraction parameters and anti-hyperglycemic assessment of standardized extract from Santalum album L. leaves - Phan Thi Kim Phung; Dang Ngoc Lam Binh; Nguyen Thi Anh Thu; Nguyen Van Ha; Tran Thi Huyen; Khuu Minh Hien; Mai Huynh Nhu; Ngo Kien Duc; Le Minh Quan (Pharmacological Research - Modern Chinese Medicine)
Background: Santalum album (SA) L., also known as sandalwood, a habituated plant in Asia and China, is commonly used in traditional Chinese medicine to treat various diseases, including inflammation and diarrhea. It is a versatile tree with considerable commercial worth, primarily due to its exceptionally fragrant qualities. Although extensively studied worldwide for its pharmacological effects, research in Vietnam has yet to develop optimized extraction processes or investigate the biological activities of SA L. constituents. Aim of the study: The objectives of this study were to establish standards, optimize extraction processes, and evaluate the hypoglycemic effects of extracts from the leaves of SA. Materials and methods: The extraction parameters for vitexin and isovitexin were optimized using response surface methodology. Vitexin and isovitexin were quantified by ultra-high-performance liquid chromatography. The hypoglycemic effect of SA extract was assessed using a male Swiss albino mouse model. Results and discussion: Quantification of vitexin and isovitexin in SA extract met the validation standards. The optimal extraction process involved refluxing at 66 °C for 180 min, using 70 % ethanol at a solvent-to-material ratio of 33:1 mL/g. Standardized extracts were developed using specified criteria for sensory properties, moisture, heavy metals, microbial limits, and compound identification. The SA extract contained 6.61 % vitexin and 4.47 % isovitexin (w/w). Safe oral SA doses of 1 and 2 g/kg were established, which improved body weight and blood glucose levels in rats with hyperglycemia. Conclusion: These findings suggest that the optimized method is effective for the extraction of vitexin and isovitexin from SA L. leaves and that the plant may serve as a potential candidate for the development of a new natural anti-diabetic agent.